PENINGKATAN KAPASITAS DAN KESADARAN LINGKUNGAN SISWA DALAM PENANGGULANGAN PENCEMARAN UDARA DI DESA MUARA PENIMBUNG - Elvi Sunarsih; Nurhayati Nurhayati; Amrina Rosyada; Rahmatillah Razak; Dwi Septiawati; Ery Erman; Fakhriyatiningrum Fakhriyatiningrum; Frisca Rahmadina; Maurend Yayank Lewinsca; Putri Utami; Dwi Fitriani; Intan Permata Sari (PARIPALAKA SRIWIJAYA, 2025)
The community service activities carried out aimed to increase environmental knowledge and awareness in efforts to overcome air pollution among elementary school students in Muara Penimbung Village. The series of activities included counseling on the introduction of basic concepts and mitigation of air pollution, distribution of pre-test and post-test questionnaires to measure changes in student knowledge. The results of the activities that have been carried out based on the analysis of pre-test and post-test data obtained an increase in student knowledge of air pollution by 97%. %. The findings of this activity indicate that educational methods are effective in increasing student knowledge and awareness of environmental issues, especially air pollution This activity is expected to be the first step in raising environmental awareness and able to increase the participation of the younger generation in protecting the environment, especially maintaining air quality